Prospective evaluation of clinical profile and treatment outcome of patients presenting with polyarthritis diagnosed as rheumatoid arthritis - Neopane, Arpana; Sharma, Mona; Rayamajhi, Sumugdha (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Polyarthritis is a common presentation of patients attending medicine outpatient department. Among various causes Rheumatoid arthritis is the commonest and a well established case has distinct characteristic features. However the early presentation of this disease has not been clear thus leading to delay in treatment. The objectives of this study was to identify the various causes of polyarthritis in our clinical practice, discuss the varied clinical presentation of rheumatoid arthritis including early Rheumatoid arthritis and to evaluate the treatment response during one year follow up. Methods: Prospective longitudinal study conducted in a teaching hospital over a two years period Results: Rheumatoid arthritis was the commonest cause of polyarthritis (77.8%) with a period prevalence of 0.7%. Early presentation included atypical features like asymmetry, unilateral presentation, manifesting within 2 months to 2 years of diagnosis. 43% (n=18) of the patients had swelling and tenderness in overused joints 1.5 years prior to full clinical manifestation. Flitting or migratory joint pain not considered to be a feature of rheumatoid arthritis was also present in 14.3% (n=6) patients with mean duration of 1.5 years prior to full blown presentation. MCPJ (metacarpophalyngeal joints) and PIP (proximal interphalyngeal joints) were involved in 90%. Treatment response with Methotrexate as a single DMARD was good as compared with DAS 28 ESR score. Conclusions: RA is a common arthritis with varied clinical presentation. Recognition of early symptoms is needed for early diagnosis and initiation of DMARD. Methotrexate as a DMARD is effective and should be initiated early. DOI: http://dx.doi.org/10.3126/mjsbh.v10i2.6459 Medical Journal of Shree Birendra Hospital July-Dec 2011 10(2) 22-28